Binder-controlled pore size distribution of carbon electrodes to mitigate self-discharge of supercapacitors. (February 2023) - Chen, Cheng-Chia; Sutarsis,; Patra, Jagabandhu; Wang, Fu-Ming; Lin, Jeng-Yu; Dong, Quan-Feng; Su, Yu-Sheng; Chang, Jeng-Kuei
Abstract: Self-discharge, which refers to voltage depression when a power source is removed, is a crucial issue for supercapacitors (SCs). Self-discharge results in Coulombic efficiency loss and energy dissipation, and thus restricts the charge storage performance of SCs. A cost-effective and facile strategy for addressing self-discharge is newly developed in this work. It is found that self-discharge involves charge redistribution and Faradaic side reactions, which are closely associated with the pore size of activated carbon electrodes. Importantly, the pore size distribution (and thus self-discharge) can be controlled by the binder type. Specifically, a binder that maintains high macropore and mesopore fractions can effectively mitigate self-discharge. The fundamental reasons for this finding are examined. The effects of the charging rate, holding time at the full charging voltage, operation temperature, and charging cutoff voltage on the self-discharge of SCs prepared using various binders are investigated. The data reveal that binder selection also influences SC reliability in terms of the aging rate at elevated temperature and high voltage, leakage current, and gas evolution during operation. Graphical abstract: Image 1 Highlights: Self-discharge has long been an issue that restricts application of supercapacitors. Electrode self-discharge involves charge redistribution and Faradaic side reactions. A proper pore size distribution control of carbon electrode mitigates self-discharge. A cost-effective strategy related to binder selection suppresses self-discharge. Charging rate, temperature, and voltage all affect self-discharge rate.